Answer:
Step-by-step explanation:
If you call "5x-2x^2+1" an "equation," then you must equate 5x-2x^2+1 to 0:
5x-2x^2+1 = 0
This is a quadratic equation. Rearranging the terms in descending order by powers of x, we get:
-2x^2 + 5x + 1 = 0. Here the coefficients are a = -2, b = 5 and c = 1.
Use the quadratic formula to solve for x:
First find the discriminant, b^2 - 4ac: 25 - 4(-2)(1) = 25 + 8 = 33
Because the discriminant is positive, the roots of this quadratic are real and unequal.
-b ± √(discriminant)
Applying the quadratic formula x = --------------------------------
2a
we get:
-5 ± √33 -5 + √33
x = ----------------- = --------------------- and
2(-2) -4
-5 - √33
---------------
-4
Answer:
D (4,2)
Step-by-step explanation:
you just change the y value to the opposite sign hehe
Answer:
36 miles
Step-by-step explanation:
given:
9 hours -------> 27 miles
1 hour ----------> 27 / 9 miles
12 hours -------> (27/9) x 12 = 36 miles
Answer:
4, 4√3
Step-by-step explanation:
In a 30-60-90 triangle:
The leg opposite of the 30-degree angle is 1/2 of the hypotenuse: 8/2 = 4
The longer leg is √3 times the shorter leg: 4*√3 = 4√3
Check work: 4^2+(4√3)^2 = 8^2 --> 16+48 = 64 --> 64 = 64
Answer:
i cant read it can u do another photo
Step-by-step explanation: